Irrigation and Fertilizer Levels for the Production of Cucumber’Puang’ - Suntaree Yingjajaval; Chalermphol Markmoon (Agriculture and Natural Resources, 1993)
Table cucumber’Puang’ has short growing period and is widely grown throughout the country. However, the optimal level of irrigation and fertilizer for its production has not been reported. This study included two experiments carried out during the summers (April-May) of 1990 and 1991, in Kamphaeng Saen soil series (Typic Haplustalfs). With a split-plot design, the main plots were 3 levels of irrigation rate, namely, 100%, 150% and 200% of potential evapotranspiration (PET), based on Penman method of 15 years average data. Water was applied in furrow twice a week. The sub-plots comprised 4 levels of 2:1:1: ratio fertilizer. These were 10 kg N, 5 kg available P2O5 and 5 kg K2O per rai in the first level of application, while fertilizer levels 2, 3 and 4 were 2, 3 and 4 times the first rate, respectively. Fertilizer was split into 6 applications. The first was applied as basal, with the rest as row broadcast on weekly basis. The growing period of cucumber was 62 days. Harvest began 35-39 days after seeding. The overall average total yield of cucumber for the two experiments was 3.61 t/rai, 67% of which were marketable. The average total fruit number was 73,170 fruits/rai with the marketable percentages of 83. Increasing the irrigation rate from 100% to 150% and 200% of PET increased the total and marketable yields by 12% and 31 % respectively. Fertilizer level 1 was adequate because the yields were not significantly different among treatments. Rather, increasing the rate of fertilizer tended to lower the yield. However, fertilizer helped increase the fresh mass of cucumber plant, while irrigation levels also increased the plant mass but of no statistical significance. Yield increase in cucumber come from the increase in number of fruit. Cucumber was harvested 17-18 times during the four-week period. The pattern of harvesting yield showed that the percentages of each harvested marketable yield to the total marketable yield of the whole season were 2-4% during the first 5 days of the harvest. Then the marketable yield peaked up during days 6-12 of the harvest, afterwhich the marketable yield dropped rather markedly. During the second half of the harvest, the percentages of non-marketable yield surged to 40-50% of the total yield. Most of the cull had curling shape with no development of the upper part of the fruit. The pattern remained fairly the same under all treatments and in both experiments. Therefore, neither the experimental treatments nor the different air temperature regimes during flower fertilization period was likely to be the cause. It was postulated that the fruit deformation was due to the inadequate supply of photosynthate to the fruit. The reduction in functioning leaf area may be due to the shading effect of the fully expanding plant and also by the increasing infection of downy mildew. The disease started on the first three leaves in the lower part of the plant, mostly since the beginning of the harvest. Stopping the application of fungicide after the first week of the harvest led to the greater injury of the leaves and the higher proportion of abnormality in fruit shape.